Optimum conditions of in vitro proliferation of splenic lymphocyte from Chinese soft-shelled turtle (Trionyx sinensis) - LI Xiao-liang; LIU Gang; ZHANG Yan-ming; SHUAI Jiang-bing; FANG Wei-huan (浙江大学学报. 农业与生命科学版, 2008)
In order to optimize the conditions for in vitro proliferation of splenic lymphocyte of Chinese Soft-shelled turtle (Trionyx sinensis), four main parameters were tested including different kinds and concentrations of mitogens, cell density and incubation time. By colorimetric method utilizing MTT [3- (4, 5-dimethylthiazol-2-yl) -2, 5-diphenyltetrazolium bromide], the lymphocyte at a density of 2×106 cells·mL-1 incubated with 10 μg·mL-1 concanavalin A (Con A) for 120 hours or 5 μg·mL-1 phytohaemagglutinin (PHA) for 144 hours was finally determined as the optimum conditions for proliferation. The results above indicate that MTT might be a reliable method for in vitro proliferation of splenic lymphocyte in Chinese soft-shelled turtle.